Hubungan antara Indeks Prestasi Kumulatif dan Nilai OSCE Komprehensif Mahasiswa - Putu Ayu Jaya Switi; Rima Kusuma Ningrum; I Made Pariartha (Aesculapius Medical Journal, 2024)
Medical education is constantly evolving to suit the needs of students, faculty, and society. With the development of Miller's pyramid theory, since the mid-20th century Objective Structured Clinical Examination (OSCE) has become an assessment standard to measure the improvement of clinical skills in medical training. OSCE is an evaluation method to assess clinical skills in medical undergraduate stage in a structured manner, which tests several aspects, namely knowledge, psychomotor, and attitude aspects. Clinical reasoning ability is one of the indicators that can be seen in the Grade Point Average (GPA). The cognitive aspect includes all knowledge gained through lectures, self-study activities, and group discussions. This aspect is tested with a Multiple Choice Question (MCQ) in the exam at the end of the block. It is still unknown whether OSCE scores can reflect students' clinical reasoning skills, because only a few studies have explained the effectiveness of OSCE to evaluate medical students' clinical reasoning skills. The purpose of this study was to determine the relationship between GPA and comprehensive OSCE scores in 105 students of class 2018 of the Faculty of Medicine and Health Sciences, Warmadewa University. The results showed that most students had a GPA> 3.50 and OSCE scores of 80.00 - 100.00. Bivariate analysis showed a strong relationship between GPA and Comprehensive OSCE scores with a correlation coefficient of 0.796.